Shift in the timing of microvascular free tissue transfer failures in head and neck reconstruction. (9th July 2019) - Sweeny, Larissa; Topf, Michael; Wax, Mark K.; Rosenthal, Eben L.; Greene, Benjamin J.; Heffelfinger, Ryan; Krein, Howard; Luginbuhl, Adam; Petrisor, Daniel; Troob, Scott H.; Hughley, Brian; Hong, Steve; et al.
Abstract : Objective: Analyze the cause and significance of a shift in the timing of free flap failures in head and neck reconstruction. Study Design: Retrospective multi‐institutional review of prospectively collected databases at tertiary care centers. Methods: Included consecutive patients undergoing free flap reconstructions of head and neck defects between 2007 and 2017. Selected variables: demographics, defect location, donor site, free flap failure cause, social and radiation therapy history. Results: Overall free flap failure rate was 4.6% (n = 133). Distribution of donor tissue by flap failure: radial forearm (32%, n = 43), osteocutaneous radial forearm (6%, n = 8), anterior lateral thigh (23%, n = 31), fibula (23%, n = 30), rectus abdominis (4%, n = 5), latissimus (11%, n = 14), scapula (1.5%, n = 2). Forty percent of flap failures occurred in the initial 72 hours following reconstruction (n = 53). The mean postoperative day for flap failure attributed to venous congestion was 4.7 days (95% confidence interval [CI], 2.6–6.7) versus 6.8 days (CI 5.3–8.3) for arterial insufficiency and 16.6 days (CI 11.7–21.5) for infection ( P < .001). The majority of flap failures were attributed to compromise of the arterial or venous system (84%, n = 112). Factors found to affect the timing of free flap failure included surgical indication ( P = .032), defect location ( P = .006), cause of the flap failure ( P < .001), and use of an osteocutaneous flap ( P = .002). Conclusion: This study is the largest to date on late free flap failures with findings suggesting a paradigm shift in the timing of flap failures. Surgical indication, defect site, cause of flap failure, and use of osteocutaneous free flap were found to impact timing of free flap failures. Level of Evidence: 4 Laryngoscope, 130:347–353, 2020